The expression of glucocorticoid and mineralocorticoid receptors in pituitary tumors causing Cushing’s disease and silent corticotroph tumors - Kober, Paulina; Rusetska, Natalia; Mossakowska, Beata J.; Maksymowicz, Maria; Pękul, Monika; Zieliński, Grzegorz; Styk, Andrzej; Kunicki, Jacek; Działach, Łukasz; Witek, Przemysław; Bujko, Mateusz (Frontiers in Endocrinology, 2023)
Objective. Pituitary neuroendocrine corticotroph tumors commonly cause Cushing’s disease (CD) that results from increased adrenocorticotropic hormone (ACTH) secretion by the pituitary tumor and consequent increase of cortisol levels in blood. However, in some patients, corticotroph tumors remain subclinical. Cortisol secretion is regulated by the hypothalamic–pituitary–adrenal axis and includes a negative feedback between cortisol and ACTH secretion. Glucocorticoids reduce ACTH level both by hypothalamic regulation and acting on corticotrophs via glucocorticoid (GR) and mineralocorticoid (MR) receptors. The aim of the study was to determine the role of GR and MR expression at mRNA and protein levels in both functioning and silent corticotroph tumors. Methods. Ninety-eight patients were enrolled, including 70 with CD and 25 with silent corticotroph tumors. Gene expression levels of NR3C1 and NR3C2 coding for GR and MR, respectively, were determined with qRT-PCR in the two tumor types. GR and MR protein abundance was assessed with immunohistochemistry. Results. Both GR and MR were expressed in corticotroph tumors. Correlation between NR3C1 and NR3C2 expression levels was observed. NR3C1 expression was higher in silent than in functioning tumors. In CD patients NR3C1 and NR3C2 levels were negatively correlated with morning plasma ACTH levels and tumor size. Higher NR3C2 was confirmed in patients with remission after surgery and in densely granulated tumors. Expression of both genes and GR protein was higher in USP8-mutated tumors. Similar relationship between USP8 mutations and expression levels were observed in analysis of silent tumors that also revealed a negative correlation between GR and tumor size and higher NR3C1 expression in densely granulated tumors. Conclusions. Although the associations between gene/protein expression and patients clinical features are not strong, they consistently show an evident trend in which higher receptor expression corresponds to more favorable clinical characteristics.